Aqueous-phase differentiation and speciation of Fe3+ and Fe2+ using water-stable photoluminescent lanthanide-based metal-organic framework - Maity, Rahul; Chakraborty, Debanjan; Nandi, Shyamapada; Yadav, Ankit Kumar; Mullangi, Dinesh; Vinod, C. P.; Vaidhyanathan, Ramanathan (ACS Applied Nano Materials, 2019)
Fe2+ is vital to O-2 transportation and photosynthesis regulated by oxidases and reductases. On the other hand, Fe3+ is detrimental due to its irreversible binding to O-2. Hence there is a need for selective identification of Fe3+ from aqueous systems in the presence of Fe2+. However, given their close chemical nature, it is not straightforward to differentiate them. Fe2+ and Fe3+ are typically sensed and differentiated using magnetic measurements, Mossbauer, X-ray absorption spectroscopy, or EXAFS, which are complex and equipment intensive techniques. In comparison, the fluorescence technique is advantageous in terms of time and accessibility. Although readily available lanthanide salts exhibit fluorescence, they are weak, and to serve as an optical probe, their luminescence has to be enhanced via ligand design. Hence we have designed a chromophoric ligand that can covalently bind to lanthanides and enhance its fluorescence intensity, and it binds selectively to Fe3+ through its nitrogen centers. It detects Fe3+ from low concentration (similar to 100 mu M) aqueous solutions, with fast response time (<1 min) and with a detection limit of 3.6 ppm. Importantly, the Fe3+ adsorbed MOF can be readily reactivated for the next cycle by merely washing with an aqueous ascorbic acid solution and can be used for multiple cycles without any appreciable loss in activity. This makes the Ln-MOF an environmentally benign, cost-effective, scalable, and recyclable probe.
Keywords: Fe3+ differentiation and speciation; flexible ligand; fluorescent MOF; iron speciation; Metal-organic framework; water sorption

Carbon derived from soft pyrolysis of a covalent organic framework as a support for small-sized RuO2 showing exceptionally low overpotential for oxygen evolution reaction - Chakraborty, Debanjan; Nandi, Shyamapada; Illathvalappil, Rajith; Mullangi, Dinesh; Maity, Rahul; Singh, Santosh K.; Haldar, Sattwick; Vinod, Chathakudath P.; Kurungot, Sreekumar; Vaidhyanathan, Ramanathan (ACS Omega, 2019)
Electrochemical water splitting is the most energy-efficient technique for producing hydrogen and oxygen, the two valuable gases. However, it is limited by the slow kinetics of the anodic oxygen evolution reaction (OER), which can be improved using catalysts. Covalent organic framework (COF)-derived porous carbon can serve as an excellent catalyst support. Here, we report high electrocatalytic activity of two composites, formed by supporting RuO2 on carbon derived from two COFs with closely related structures. These composites catalyze oxygen evolution from alkaline media with overpotentials as low as 210 and 217 mV at 10 mA/cm(2), respectively. The Tafel slopes of these catalysts (65 and 67 mV/dec) indicate fast kinetics compared to commercial RuO2. The observed activity is the highest among all RuO2-based heterogeneous OER catalysts-a touted benchmark OER catalyst. The high catalytic activity arises from the extremely small-sized (similar to 3-4 nm) RuO2 nanoparticles homogeneously dispersed in a micro-mesoporous (BET = 517 m(2)/g) COF-derived carbon. The porous graphenic carbon favors mass transfer, while its N-rich framework anchors the catalytic nanoparticles, making it highly stable and recyclable. Crucially, the soft pyrolysis of the COF enables the formation of porous carbon and simultaneous growth of small RuO2 particles without aggregation.

Three in one: triple G-C-T base-coded brahma nucleobase amino acid: synthesis, peptide formation, and structural features - Wagh, Mahendra A.; Maity, Rahul; Bhosale, Rohit J.; Semwal, Divyam; Tothadi, Srinu; Vaidhyanathan, Ramanathan; Sanjayan, Gangadhar J. (Journal of Organic Chemistry, 2021)
This note reports the synthesis and peptide formation of a novel triple G-C-T nucleobase amino acid (NBA) building block featuring three recognition faces: DDA (G mimic), DAA (C mimic), and ADA (T mimic). Readily obtainable in multigram scale in a remarkably easy one-step reaction, this unique NBA building block offers scope for wide ranging applications for nucleic acid recognition and nucleic acid peptide/protein interaction studies.